Remoção de fósforo de unidade de flotação da estação de tratamento de esgoto - Machado, Fernando Ruas (2007)
The flotation made by dissolved air (DFA) is an effective technology on the removal of the phosphorus during the treatment of the sewage system. The city of Uberlândia, nowadays, treats the whole domestic sewage, through three stations equipped with anaerobic reactors followed by the units of flotation. The sewage systems normally present between 4 and 15 mg / L of phosphate (METCALF; EDDY,1991). The phosphorus that is found in the sewage system under the format of phosphate is the most important limiting factor of the productivity in the most of the continental waters, being responsible for the artificial eutrophication . It s necessary to promote the chemical coagulation and the flocculation of the scattered particles in the water so that the flotation of the sewage system becomes successful. The hydrophobicity, the presence of micro air bubbles, and the chemical products added to the tributary, are also essential factors in the flotation process. The operation of flotation unit involves many variables, and the most important are the outflow of the air, the velocity of the dredging machine, the concentration of coagulant and polymer. This way, the planning and analysis of the experiments are more trustworthy, when statistic techniques are used. The determination of a relationship between the variables of the process and the removal of phosphorus provides a better evaluation of the efficiency of the flotation unit. From this perspective, a central compound planning was made to determine the equation of the removal of the phosphorus because of the outflow of the air, the velocity of the dredging machine, the concentration of coagulant and polymer. According to the main experimental results the average of the efficiency was 85% on the flotation unit, which provided an improvement of the environmental quality of the hydric body that receives the treated effluents. The variables of the concentration of coagulant and the outflow of the air influence significantly on the removal of the phosphorus. The cationic polymer used through this work did not prove efficient on the treatment of the pos reactor effluent. The best operational conditions for ETEIpanema were determined on the intermediary level of the experimental range used ( the concentration of coagulant of 80 ppm, the polymer concentration of 2,5 ppm, the velocity of the dredging machine of 1,15 RPM and the outflow of the air of 20 L/s), since high values of phosphorus removal was reached together with a decrease of the use of inputs and a lesser wearing of the unit of flotation.